Study of Genetic Improvement Techniques of Terminalia chebula Retz. - an Important Multipurpose Medicinal Tree Species of India - Ramesh Singh, D. R.; Dhir, K. K.; Vij, S. P.; Nayyar, H.; Singh, Kamaljit (Indian Forester, 2003)
Terminalia chebula Retz. is a multipurpose medicinal plant found in all deciduous forests of India. It is a hardy moderate size tree species that can grow with very little care and can be integrated in to farm forestry profitably. Full potential for revegetating Siwalik hills requires to be exploited throughout North India. Studies were carried out on three provenances of Haryana State to ascertain regeneration status of this important indigenous tree that was considered only as a source of NWFP of medicinal and dyeing fruits. Studies have indicated it produces firewood and , in scarcity time , fodder also. Natural variation in fruits have been found to be heritable and beneficial variations could be harnessed to make this tree more acceptable to farmers. Under a programme called 'TREIMP' sustained efforts are being made to produce seedlings and supply to the growers without loss of time involved in transfer of technology.